Perancangan Sistem Informasi Jual Beli Properti “BWR Property” Berbasis Web Terintegrasi - Putra, I Wayan Weda Adi; Januarta, I Komang Bagus; Romeo, Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The high market demand for residential and commercial properties today requires a fast, transparent, and easily accessible information platform for the wider community. Therefore, this research was conducted to design and develop